Transfer Of Criminal Activities From One Country To Other - Desy Kartika C Sitepu (Journal of Law Science, 2021)
Extradition is defined as the surrender of criminals from one country to another. The purpose and objective of extradition is to ensure that the perpetrators of serious crimes cannot escape prosecution or punishment. Therefore, it is appropriate and appropriate for the criminal to be handed over for examination and trial by a state having jurisdiction. The issue raised is the extradition procedure according to Law Number 1 of 1979, the types of crimes that can be requested for the transfer of the perpetrators of criminal acts. The method used is a normative juridical approach, namely research based on literature study. The literature study was conducted to find secondary data, while secondary data were primary legal materials in the form of criminal law literature, extradition and other secondary legal materials. Meanwhile, the tertiary legal materials used in this paper are materials obtained from the internet. Extradition procedures according to Law Number 1 of 1979 are conditions that must be carried out in the process of transferring criminals from one country to another. The perpetrator of a criminal act who can be extradited is any person whom the competent authority from a foreign country requests from Indonesia, on the basis that the person concerned is suspected of committing a crime in order to be able to serve a sentence, while a crime that cannot be extradited is a political crime.